#TITLE_ALTERNATIVE# - MUKHLIS ASHSHIDDIQI (NIM 10105085), MOHAMMAD
L4(2,1)-labelling is a labelling used to label interference graph, where its vertices represent radio transmitters, and every two vertex is connected by an edge. A label of a vertex of G represent radio channel and every edge of G has a weight that represents interference between the cosserponding radio frequencies. We study an application radio labelling problem in Bandung and propose recommended frequencies for FM radios in Bandung deduced from L4(2,1)-labelling.